Field-Obtained Soil-Water Characteristic Curves of KPK Expansive Soil and Their Prediction Correlations. (21st November 2020) - Zamin, Bakht; Nasir, Hassan; Mehmood, Khalid; Iqbal, Qaiser
Abstract : Expansive clays are found worldwide in arid and semiarid regions. Such soils are considered a natural hazard for civil engineering infrastructures especially when they are lightly loaded. Expansive soils are often unsaturated due to the high absorption capacity of moisture. The damaging effect of expansive soils is intimately related to the distinctive soil-water characteristic in the surficial soil layers subjected to wetting-drying cycles. The soil-water characteristic curve (SWCC) also known as the water-retention curve shows the fluctuation of suction with the moisture content. It is one of the key parameters that have been developed and used by soil engineers for studying the properties of partially saturated soils. Currently, the SWCCs produced by most of the researchers are grounded on lab testing which is quite different from the field-obtained curves. In the current study, the SWCCs for Karak expansive soil have been obtained from in situ testing (field). For this purpose, three sites were selected at Amberi Village (Karak) for instrumentation. An open trench of six-foot depth was excavated in each site and instrumented. Electrical resistivity sensors (G-blocks) and tensiometers were used for matric suction measurements. The gravimetric moisture content was measured with the help of moisture sensors calibrated with a speedy moisture meter. To check the fluctuation of moisture and suction, these instruments were installed at three different depths, that is, 0–2, 2–4, and 4–6 feet. Based on results, the maximum suction of 705.79 kPa was observed in the site "A" in 0–2-foot depth (near the ground surface) with a moisture content of 15 percent. The variations in suction and moisture content follow the almost same trend at low suction; however, the trend was slightly different at the moderate suction range. The measured suction showed a strong correlation with the free swell index (FSI) and moisture content. It was found that the upper layers of expansive soil have high suction than lower layers due to more exposure to the environmental agencies and low density.